Growth and maturity of belugas (Delphinapterus leucas) in Cumberland Sound, Canada, and in captivity: evidence for two growth layer groups (GLGs) per year in teeth - Brodie, P.; Ramirez, K.; Haulena, M. (J. Cetacean Res. Manage., 2023)
The beluga (Delphinapterus leucas) is one of the few cetaceans to adapt, year-round, to an Arctic environment, one of the most challenging marine habitats, incorporating shallow estuaries, high turbidity, shifting pack-ice and extreme tidal ranges. Adaptation is attributed in part, to year-round herd integrity and synchrony, occupying a sequence of restricted seasonal habitats and calving sites, which are reflected in tooth laminae. Field research, 1966–1969, led to the conclusion that females are sexually mature at 5.75 years and males at 8.75 years, gestation is 15–16 months, reproductive cycle 3 years, with a lifespan of 30–35 years. Newborn and the first four year-classes are recognisable by length, body colour and morphology. The two-year nursing period results in rapid growth, coincident with a training period to acquire social, feeding, and crucial under-ice navigational skills. Belugas in Cumberland Sound had been reduced through exploitation, thus it is unlikely that present numbers are food limited, reflecting maximum rate of increase. We examine growth indices for captive belugas, either captured as calves, or first and second generations born in captivity, to compare known-age animals. Onset of sexual maturity in males and females is similar to findings for Cumberland Sound, which was based on two growth layer groups per year in the teeth, or GLG/2. We analyse studies where previous oral doses of tetracycline, as well as bomb radiocarbon 14C from 1958 were used to argue for single annual GLGs or GLG/1. Dedicated field studies, using appropriate dosage of intramuscular tetracycline, provide evidence for GLG/2. The 14C study appears to have been compromised by preparation technique and burdens sampled in the 1990s may have been of maternal origin, transferred during foetal growth and nursing, or from recent fallout to 1980. Fundamental to the issue of growth-at-age: arguments for GLG/1 are based on back-calculation from adults of unknown age, while GLG/2 is based on projection from newborn to known-age young and adults. Direct observations and cross-referenced parameters do not substantiate GLG/1, which requires halving the growth rate, thus doubling the age of sexual and physical maturity as well as lifespan, resulting in a 40% reduction of the intrinsic rate of natural increase, substantially lower than the present rate of recovery observed.